Effect of contrast water therapy duration on recovery of running performance - Versey, N. G.; Halson, S. L.; Dawson, B. T. (International Journal of Sports Physiology and Performance, 2012)
Purpose: To investigate whether contrast water therapy (CWT) assists acute recovery from high-intensity running and whether a dose-response relationship exists. Methods: Ten trained male runners completed 4 trials, each commencing with a 3000-m time trial, followed by 8 × 400-m intervals with 1 min of recovery. Ten minutes postexercise, participants performed 1 of 4 recovery protocols: CWT, by alternating 1 min hot (38°C) and 1 min cold (15°C) for 6 (CWT6), 12 (CWT12), or 18 min (CWT18), or a seated rest control trial. The 3000-m time trial was repeated 2 h later. Results: 3000-m performance slowed from 632 ± 4 to 647 ± 4 s in control, 631 ± 4 to 642 ± 4 s in CWT6, 633 ± 4 to 648 ± 4 s in CWT12, and 631 ± 4 to 647 ± 4 s in CWT18. Following CWT6, performance (smallest worthwhile change of 0.3%) was substantially faster than control (87% probability, 0.8 ± 0.8% mean ± 90% confidence limit), however, there was no effect for CWT12 (34%, 0.0 ± 1.0%) or CWT18 (34%, -0.1 ± 0.8%). There were no substantial differences between conditions in exercise heart rates, or postexercise calf and thigh girths. Algometer thigh pain threshold during CWT12 was higher at all time points compared with control. Subjective measures of thermal sensation and muscle soreness were lower in all CWT conditions at some post-water-immersion time points compared with control; however, there were no consistent differences in whole body fatigue following CWT. Conclusions: Contrast water therapy for 6 min assisted acute recovery from high-intensity running; however, CWT duration did not have a dose-response effect on recovery of running performance.